Modelagem de um aplicativo para medir a percepção do usuário em relação à inclinação de rampas na UFPB - Miranda, Ramon Gomes de Lima (2019)
This research has as an overall objective an application to calculate a new inclination pattern for ramps (non-curves) using the user's perception. To obtain this kind of information, it is important to identify, for example: a) Identify and describe the different types of accessibility; b) Identify the measures foreseen in the Institutional Development Plan of the UFPB, regarding accessibility; and c) Describe a modeling and applicability of this model of simulations. It is a qualitative research that, according to Creswell (2010, p.43), is a means to explore and understand the sense that individuals or groups attribute a social or human problem. In relation to the objectives, this study is characterized as descriptive. When it comes to the type of research, it can be said that it deals with applied research. Regarding the methodological procedures for an application modeling usable in MIT App Inventor 2, which is an open source application. The selected object for an application modeling was a Ramp. The selection of this item is justified by the existence of a quantity of data about its execution aiming at compliance with legal requirements on accessibility. In relation to a definition of the elements, they will be used in length and height, which are listed in NBR 9050 for the slope calculation, the subjective perception of the subject, the ability to qualify and the degree of difficulty to climb the ramp, and coefficients thatereder to calculate the new incline of ramps. The database contains the duration of each ramp that is to be registered in the application, the verification of the use of the script by man as none, the minimum, the average, the maximum and the coefficients that vary, in percentage, from 0 to 26, 5 staggered according to a schedule of the current one. And, finally, the tables will be elaborated with three different intervals, where the coefficients and degrees of difficulties are present between 5% and 30% of slope. The expected results of this study include: contributing to the development of new studies on incline ramps, providing technical feasibility in the construction of accessible ramps, strengthening the relationship between what is planned and what is performed for the purpose of providing projects more aligned with the reality of people with disabilities, make available to the UFPB institution, as well as to society, an application model that can solve the problems of slope ramps from the perception of the subject, among other aspects.